Purplicious - Kann, Victoria; Kann, Elizabeth (New York : HarperCollins, 2007)
Feeling like an outcast from her classmates who all love black, Pinkalicious decides to stay true to her favorite color and learns that pink is pretty and powerful.
School Library Journal, March 2008.
Horn Book, October 2008.
1.8
K-3
AD560L
Keywords: Pink -- Juvenile fiction; Identity -- Juvenile fiction; Schools -- Juvenile fiction; Color -- Juvenile fiction; Pink -- Fiction; Identity -- Fiction; Schools -- Fiction; Color -- Fiction; Pink -- Fiction; Individuality -- Fiction; Color -- Fiction; Individuality -- Fiction; Color -- Fiction; Schools -- Fiction; School stories